People's Republic of China and Its Neighbors: Partners or Competitors for Trade and Investment? - John Weiss (Asian Development Bank Institute (ADBI), 2004)
The very rapid economic growth of the People's Republic of China (henceforth PRC), its dramatic success in world export markets and its heavy receipts of foreign direct investment (FDI) have generated much thought and debate in policy and business circles in different parts of the world. This paper surveys evidence from research by ADB Institute staff and Visiting Fellows conducted over the last two years that sheds light on these issues. The paper examines differences in trade structure between PRC and its trading partners, finding that PRC's current structure is closest to that in Korea and Taipei,China in 1990. It also considers changes in market share and finds that PRC exports are eroding the market share of its regional neighbors in the US and Japan, particularly in products in which trading partners are most specialized. There is no evidence of FDI diversion from elsewhere in the region to PRC. The trade diversion effects in the US and Japan are offset however by strong trade creation as the rapid growth in PRC leads to a substantial rise in its imports. The paper surveys the projections of models that demonstrate the gains in greater trade and income for the region from closer trade links with PRC. The broad conclusion that emerges is that whilst there may be risks to individual sectors in all countries concerned, the pattern of regional trade and investment that is emerging is mutually beneficial, provided enterprises and governments in PRC's regional partners respond effectively to the adjustments required.
hdl:11540/4166
Keywords: 330; Internationale Wirtschaftsbeziehungen; Auslandsinvestition; Außenhandelsstruktur; Internationaler Wettbewerb; China; Südostasien